2001
DOI: 10.1177/014107680109400515
|View full text |Cite
|
Sign up to set email alerts
|

A Learning-Disabled Woman who had been Raped: A Multi-Agency Approach

Abstract: was raised by the vertical position of the stent in the initial abdominal X-ray. After insertion, duodenal stents assume the C-shape of the duodenum. A vertical position might simply indicate straightening of the stent 3 . However, it could also represent migration or perforation; indeed, straightening-out might well be a risk factor for perforation.In a patient with malignant duodenal obstruction, the expected survival is only a few months 4 . Therefore the aim of stenting is to provide good palliation with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The rate of termination (18%) amongst the English women reflected the underlying rate for England and Wales (Raleigh 1998) and compared to 6% amongst the Bangladeshi women. One was the direct result of a sexual assault (O'Hara & Martin 2001) and the other involved a severely learning disabled woman who had been taken back to Bangladesh where she was married and became pregnant. However, data collection showed that terminations, though known to practitioners, were rarely documented in clinical notes and that specialist emotional support was not offered.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of termination (18%) amongst the English women reflected the underlying rate for England and Wales (Raleigh 1998) and compared to 6% amongst the Bangladeshi women. One was the direct result of a sexual assault (O'Hara & Martin 2001) and the other involved a severely learning disabled woman who had been taken back to Bangladesh where she was married and became pregnant. However, data collection showed that terminations, though known to practitioners, were rarely documented in clinical notes and that specialist emotional support was not offered.…”
Section: Discussionmentioning
confidence: 99%
“…Still less cases of serious sexual abuse or assault are actually dealt with by the courts. 6,7 However, a person with limited communication skills can be assisted by the use of dolls, drawings or models. As with abuse in children, this needs to be performed by a person with appropriate skills and training to avoid leading questions.…”
Section: Sexual Abusementioning
confidence: 99%
“…3 If appropriate methods are used, even a person with severe disability may be able to report abuse and make decisions about how to proceed. 7 The best protection has been shown to be sexual abuse knowledge 5 so there is a very real place for education programmes to reduce the risk of sexual abuse.…”
Section: Sexual Abusementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, people with disabilities are more vulnerable to sexual assault than the general public. Reasons for vulnerability also include poor understanding of the nature of the disability and the limitations presented by it, difficulty negotiating equality in relationships and difficulty reporting abuse (O'Hara & Martin, 2001;Valenti-Hein, 2000). Also, persons with the disability may themselves not feel that they have a right to make their own decisions about sex because of their upbringing, or they may be manipulated into an abusive relationship by means of rewards or flattery (Polusny & Follette, 1995).…”
Section: Shutterworth and Monamentioning
confidence: 99%